Capsaicin Is a Negative Allosteric Modulator of the 5-HT3 Receptor - Nebrisi, Eslam El; Prytkova, Tatiana; Lorke, Dietrich Ernst; Howarth, Luke; Alzaabi, Asma Hassan; Yang, Keun-Hang Susan; Howarth, Frank C.; Oz, Murat (Frontiers in Pharmacology, 2020)
In this study, the effects of capsaicin, an active ingredient of the capsicum plant, were investigated on human 5-hydroxytryptamine type 3 (5-HT3) receptors. Capsaicin reversibly inhibited serotonin (5-HT)-induced currents recorded by the two-electrode voltage-clamp method in Xenopus oocytes. The inhibition was time and concentration-dependent with an IC50 = 62 μM. The effect of capsaicin was not altered in the presence of capsazepine, and by intracellular BAPTA injections or trans-membrane potential changes. In radioligand binding studies, capsaicin did not change the specific binding of the 5-HT3 antagonist [3H]GR65630, indicating that it is a noncompetitive inhibitor of the 5-HT3 receptor. In HEK-293 cells, capsaicin inhibited 5-HT3 receptor-induced aequorin luminescence with an IC50 of 54 µM and inhibition was not reversed by increasing concentrations of 5-HT. In conclusion, the results indicate that capsaicin acts as a negative allosteric modulator of human 5-HT3 receptors.